A complex network approach to clinical science. (5th July 2018) - Hofmann, Stefan G.; Curtiss, Joshua
Abstract: Contemporary classification systems assume that psychiatric disorders are expressions of latent disease entities. However, some critics point to the comorbidity problem and other issues that question the validity of the latent disease model. An alternative to this traditional view is the complex network approach. This approach assumes that disorders exist as systems of inter‐connected elements, without requiring that the elements are expressions of latent disease entities. Depending on the structure of the network, change can occur abruptly once the network reaches a tipping point. A dynamic complex network approach could be used to develop a functional analytic case conceptualization that may predict treatment change, relapse and recovery, thereby linking nosology and treatment. In conclusion, the complex network perspective offers an alternative and less restrictive approach to the latent disease model, while offering exciting new directions for future research in psychiatry.